Emprendimiento: Un análisis Desde el enfoque de género - Ayos Figueroa, Nacira (Corporación Universitaria Americana, 2022)
It is a great satisfaction to close my cycle contributing to the strengthening of the profession of Business Administration, in my capacity as Executive Director of the Professional Council of Business Administration - CPAE during the years 2012 - 2022; even more from the effort that from this council has been made year after year with the aim of energizing bets for the positioning of its professionals and supporting research on reflections of their work in the territories.